Mini Hydro Electric Generator with Monitoring System - Ibrahim, Muhammad Izzat Izdihar; Mohd Muji, Siti Zarina (Evolution in Electrical and Electronic Engineering, 2026)
This project focuses on designing and developing a prototype of a mini-hydroelectric generator integrated with a real-time monitoring system using Blynk software. The system monitors key parameters such as voltage, battery level, power output, and efficiency, with data collected and displayed via an ESP32 microcontroller and a user-friendly mobile interface. A 3D-printed vertical axis turbine is used to convert the kinetic energy of flowing water into electrical energy, successfully generating approximately 5.39V DC to power basic devices like lights and fans. The project demonstrates the potential of small-scale hydroelectric systems as a sustainable and environmentally friendly energy source, especially in rural areas with limited access to electricity. Future improvements may involve using more efficient brushless DC motors, advanced microcontrollers, and optimized turbine designs, with further field testing to enhance performance and reliability. This work contributes to the development of renewable energy technologies for rural power applications.